Commutation failure and voltage sensitivity analysis in a hybrid multi‐infeed HVDC system containing modular multilevel converter. (18th March 2016) - Guo, Qinglei; Yoon, Minhan; Kim, Chanki; Jang, Gilsoo
Summary: A typical hybrid dual‐infeed high‐voltage direct current (HVDC) system includes two types of links—line‐commutated converter (LCC) HVDC and voltage‐source converter (VSC) HVDC in proximity. When faults occur in the LCC‐HVDC side, the VSC‐HVDC link sufficiently can compensate power to the LCC‐HVDC system; thus, voltage fluctuation is suppressed. In recent years, the modular multilevel converter (MMC) has been a promising type of VSC. This paper presents a novel hybrid dual‐infeed HVDC system consisting of an LCC‐HVDC link and an MMC‐HVDC link, and the two links are interconnected through a tie line between buses in the inverter side. The positive contribution of the MMC‐HVDC link to the LCC‐HVDC link in the area of commutation failure immunity index, effective short circuit ratio, voltage sensitivity factor, temporary overvoltage, and DC line fault recovery are investigated. Investigations show that the stability of system has been enhanced significantly with MMC, and the contributors are physical structure change and the control strategy of the MMC‐HVDC system. The modelling and simulation of the steady state and transient performance of hybrid HVDC system are conducted in PSCAD/EMTDC. Finally, the simulation results verify the enhancement in sensitivity and stability of the dual‐infeed HVDC system. Copyright © 2016 John Wiley & Sons, Ltd.